Dynamics of Thermolysis and Skin Microstructure in Water Buffaloes Reared in Humid Tropical Climate—A Microscopic and Thermographic Study - Vilela, Reíssa Alves; Lourenço Junior, José de Brito; Jacintho, Manuel Antonio Chagas; Barbosa, Antonio Vinícius Correa; Pantoja, Messy Hannear de Andrade; Oliveira, Carlos Magno Chaves; Garcia, Alexandre Rossetto (Frontiers in Veterinary Science, 2022)
The thermolytic capacity test is used to assess the adaptability of animals to existing environmental conditions. However, there is insufficient information on the relationship between histomorphometry and adaptability of buffaloes. Thus, this study aimed to assess the use of thermolysis pathways by buffaloes reared in a hot and humid environment so as to understand the relationships between environment, skin morphological characteristics, and heat storage, as well as the intensity and proportionality of use of its ways of dissipating heat to maintain homeothermy. The heat tolerance test, associated with evaluations via infrared thermography, was applied to ten female Murrah buffaloes and tegument histomorphometry was carried out. The animals exhibited very high heat tolerance with an average of 9.66±0.21 and used thermal polypnea as the main heat dissipation pathway. Their mean skin thickness was 6.03±1.16 mm and the percentages of active sweat and sebaceous gland tissue were 1.57±0.38 and 1.08±0.39 %, respectively. The buffaloes exhibited a positive correlation between eyeball temperature and internal body temperature (r=0.84523, P<.0001) and a negative correlation between respiratory rate and skin thickness (r=-0.73371, P=0.0157). The high thermolytic capacity in shade conditions confirms the importance of access to shade in buffalo rearing systems in tropical regions.